Does sex affect second ACL injury risk? A systematic review with meta-analysis - Patel, A. D.; Bullock, G. S.; Wrigley, J.; Paterno, M. V.; Sell, T. C.; Losciale, J. M. (British Journal of Sports Medicine, 2021)
Objective: To determine sex-based differences in risk of a second ACL injury (overall and by laterality) following primary ACL reconstruction in athletes who are attempting to return to sport. Design: Systematic review with meta-analysis. Data sources: Systematic search of five databases conducted in August 2019. Eligibility criteria for selecting studies: Studies reporting sex-based differences in the incidence of second ACL injury in athletes attempting to return-to-sports and who were followed for at least 1 year following primary ACL reconstruction. Results: Nineteen studies were included in this review, with seven studies excluded from the primary meta-analysis due to high risk of bias. The remaining 12 studies (n=1431 females, n=1513 males) underwent meta-analysis, with all 19 studies included in a sensitivity analysis. Total second ACL injury risk was 21.9% (females: 22.8%, males: 20.3%). Females were found to have 10.7% risk of an ipsilateral ACL injury and 11.8% risk of a contralateral ACL injury. Males were found to have 12.0% risk of an ipsilateral ACL injury and 8.7% risk of a contralateral ACL injury. No statistically significant differences were observed for total second ACL injury risk (risk difference=-0.6%, 95% CI -4.9 to 3.7, p=0.783, I2=41%) or contralateral ACL injury risk (risk difference=1.9%, 95% CI -0.5% to 4.4%, p=0.113, I2=15%) between sexes. Females were found to have a 3.4% absolute risk reduction in subsequent ipsilateral ACL injury risk compared with males (risk difference=-3.4%, 95% CI -6.7% to -0.02%, p=0.037, I2=35%).Conclusion: Both sexes have 20% increased risk of experiencing a second ACL injury. Any difference in the absolute risk of either a subsequent ipsilateral or contralateral ACL injury between sexes appears to be small.